MODEL KOMUNIKASI KEPALA DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI DESA TIMORENG PANUA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Syarifuddin, Sarinah; R, Muhammad Rais Rahmat; Mustanir, Ahmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to analyze the communication model implemented by the Village Head in efforts to increase community participation in Timoreng Panua Village, Panca Rijang District, Sidenreng Rappang Regency. The study uses a descriptive qualitative approach to explore how the Village Head applies an effective communication model to encourage community involvement in the village development process. The findings indicate that the communication carried out by the Village Head successfully involved various elements of the community and village government, contributing to increased community participation in development activities. However, community participation is still not optimal, especially in decision-making related to village development plans. This research is expected to contribute both theoretically and practically to the development of more effective communication models to enhance community participation at the village level.